Is the tumor-stroma ratio a prognostic factor in gallbladder cancer? - Uzun,Mehmet Ali (2022)
SUMMARY OBJECTIVE: This study aimed to examine the prognostic effect of the tumor-stroma ratio, which has been shown to have prognostic value in various cancers, in patients with gallbladder cancer who have undergone curative resection. METHODS: The records of gallbladder cancer patients who underwent surgical treatment in our clinic between December 2005 and March 2021 were analyzed retrospectively. The hematoxylin and eosin-stained sections representing the tumors were evaluated under light microscopy to determine tumor-stroma ratio, and based on the results, <50% was defined as the stroma-rich and ≥50% as the stroma-poor groups. RESULTS: A total of 28 patients, including 20 females and 8 males, with a mean age of 64.6 years, were included in this study. Stroma-poor and stroma-rich tumors were detected in 15 and 13 patients, respectively. There was no statistically significant relationship identified between tumor-stroma ratio and advanced age, gender, serum levels of carbohydrate antigen 19-9 and carcinoembryonic antigen, incidental or nonincidental diagnosis, jaundice, adjacent organ or structure resection, tumor location, grades 1–2 or 3, T1/T2 or T3/T4, N0 or N1/N2, M stage, American Joint Committee on Cancer stage, lymphovascular invasion, and perineural invasion. The stroma-poor and stroma-rich groups had a 5-year survival rate of 30% and 19.2% and a median overall survival of 25.7 and 15.1 months, respectively, with no statistically significant difference between the groups (p=0.526). CONCLUSIONS: A low tumor-stroma ratio tended to be a poor prognostic factor in gallbladder cancer, although not to a statistically significant degree. This can be considered one of the preliminary studies, as further studies involving larger groups are needed.